Identification of Gene Expression Profiles Associated with an Increased Risk of Post-Operative Recurrence in Crohn's Disease. (10th February 2022) - Ngollo, Marjolaine; Perez, Kevin; Hammoudi, Nassim; Gorelik, Yuri; Delord, Marc; Auzolle, Claire; Bottois, Hugo; Cazals-Hatem, Dominique; Bezault, Madeleine; Nancey, Stéphane; Nachury, Maria; Treton, Xavier; et al.
Abstract: Background and Aims: Ileocolonic resection is frequently needed in the course of Crohn's disease [CD] treatment and post-operative recurrence is extremely common. Our main objective was to analyse gene expression in the mucosa of CD patients at the time of surgery and at post-operative endoscopy, in order to identify predictors and mechanisms of early endoscopic recurrence. Methods: We conducted transcriptome analyses on ileal mucosa samples collected from inflamed sections of the surgical specimens [ n = 200], from ileal resection margins [ n = 149] and in the neo-terminal ileum 6 months after surgery [ n = 122]; these were compared with non-inflammatory bowel disease controls [ n = 25]. The primary endpoint was post-operative endoscopic recurrence at 6 months. We applied regression models to identify gene signatures predicting endoscopic recurrence. Results: Chronic inflammation was associated with strong expression of inflammatory genes [IL-6, IL-8, IL-1B] and decreased expression of genes involved in metabolic processes, but with a high inter-individual heterogeneity. Gene signatures associated with early endoscopic recurrence were mainly characterized by upregulation of TNF α, IFN γ, IL23A and IL17A . Pathway analyses showed that upregulation of mitochondrial dysfunction within the inflamed sections and JAK/STAT at the ileal margin were predictive of post-operative recurrence. A combined model integrating these top pathway signatures improved the prediction of endoscopic recurrence [area under the curve of 0.79]. STAT3 phosphorylation at the surgical ileal margin was associated with severe recurrence at 6 months. Conclusion: We identified several biological pathways in surgical ileal mucosa specimens associated with an increased risk of disease recurrence. Integration of the JAK/STAT and mitochondrial dysfunction pathways in the clinical model improved the prediction of post-operative recurrence.